2017
DOI: 10.1136/bmjopen-2016-013821
|View full text |Cite
|
Sign up to set email alerts
|

What does patient feedback reveal about the NHS? A mixed methods study of comments posted to the NHS Choices online service

Abstract: ObjectiveTo examine the key themes of positive and negative feedback in patients’ online feedback on NHS (National Health Service) services in England and to understand the specific issues within these themes and how they drive positive and negative evaluation.DesignComputer-assisted quantitative and qualitative studies of 228 113 comments (28 971 142 words) of online feedback posted to the NHS Choices website. Comments containing the most frequent positive and negative evaluative words are qualitatively exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
50
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 37 publications
3
50
0
Order By: Relevance
“…The perception that most online feedback is negative is not supported by previous work which shows that most is largely positive in nature 27,28 and covers similar areas to those obtained through more traditional feedback routes. 29 Furthermore, it has been demonstrated that motivations for leaving feedback are more likely to be for praising a service rather than making a complaint.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…The perception that most online feedback is negative is not supported by previous work which shows that most is largely positive in nature 27,28 and covers similar areas to those obtained through more traditional feedback routes. 29 Furthermore, it has been demonstrated that motivations for leaving feedback are more likely to be for praising a service rather than making a complaint.…”
Section: Discussionmentioning
confidence: 65%
“…1 It is worth noting that a study by Brookes and Baker examining the content of patient feedback left on NHS Choices found that while most feedback is positive, the interpersonal skills of medical staff were one of the most frequently negatively evaluated aspects of care. 27 Negative evaluation of interpersonal skills may therefore resonate more strongly with clinicians (because it is commenting on something personal about them as individuals) compared to a positive evaluation of something less personal, such as administrative processes or waiting times. This perhaps explains the perception that online feedback is negative and the view that it may encourage personal attacks.…”
Section: Discussionmentioning
confidence: 99%
“…32 CL is a branch of linguistics that focuses on analysing patterns of co-occurrence and meanings in corpus data 33,34 ; its application can bring new insights to research questions. 35 CL has previously been demonstrated as useful for health-related research related to communication [36][37][38][39][40] and, therefore, was considered suitable for this study. CL techniques allowed pattern-identification of important content items (research question 1) and GP views on patients receiving letters (research question 2).…”
Section: Discussionmentioning
confidence: 99%
“…The study suggested patients’ perceptions for possible areas of improvement within various aspects of NHS service provision. High priority was given to the interpersonal aspects of healthcare provider interaction as well as system or organisational issues in coordinating services 43. Similarly, by involving the user in a participatory design ensures consumers’ requested functionalities can be incorporated to optimise the usability of the potential solution and simultaneously empower healthcare providers 44…”
Section: Discussionmentioning
confidence: 99%